2010
DOI: 10.3402/fnr.v54i0.5402
|View full text |Cite
|
Sign up to set email alerts
|

Do study circles and a nutritional care policy improve nutritional care in a short- and long-term perspective in special accommodations?

Abstract: BackgroundDisease-related malnutrition is a major health problem in the elderly population and management issues are under-explored.ObjectivesWhat is the prevalence of undernutrition-risk (UN-risk), underweight, and overweight in special accommodations (SAs)? Do study circles and a nutritional care policy (NCP) improve the precision in nutritional care (NC) and decrease the prevalence of under- and overweight in a short- and/or long-term perspective?DesignQuasi-experimental pre- and post-intervention design wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 20 publications
1
39
0
1
Order By: Relevance
“…The positive evaluation of the personnel was shown in another study that the attitudes of professionals in relation to the introduction of something new in their daily routines is related to their professional background (Christensson et al, 2010;Landstrom, Sidenvall, Koivisto Hursti, & Magnusson, 2007;Scott-Samuel & Springett, 2007;Westergren & Hedin, 2010). Those professionals who have a higher educational and professional background and level of possibility to see the big picture and the possible benefits of a new service are more optimistic (Landstrom, et al, 2007).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive evaluation of the personnel was shown in another study that the attitudes of professionals in relation to the introduction of something new in their daily routines is related to their professional background (Christensson et al, 2010;Landstrom, Sidenvall, Koivisto Hursti, & Magnusson, 2007;Scott-Samuel & Springett, 2007;Westergren & Hedin, 2010). Those professionals who have a higher educational and professional background and level of possibility to see the big picture and the possible benefits of a new service are more optimistic (Landstrom, et al, 2007).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Another study showed that nutrition study circles and a nutritional care policy improve nutritional care in both the short-and long-term perspective (Westergren & Hedin, 2010). The present study shows that there is still a need to work on routines and ways of changing any negative attitudes among the personnel related to food preparation as a work task.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In 2004, joint guidelines were drawn up and developed regarding how to detect those at risk for malnutrition, which in 2005, contributed as input to the fi rst large scale point prevalence study in Sweden on eating and nutrition (13). Th is study was followed up by two further studies in 2007 and 2009 that showed some improvement in nutritional care following an educational intervention (14)(15)(16). One indicator of success appeared to be due to the relatively fast feedback to each unit that had the ability to compare its performance with their own community or hospital (14).…”
Section: Contextmentioning
confidence: 99%
“…Nine studies (28-30, 38, 40, 41, 44, 46, 47) took place in the acute setting, 8 (26,33,37,39,42,43,45,48) in nursing homes, 5 (25,31,32,34,36) in the community, and 2 (27,35) in sheltered accommodation. Sample sizes ranged from 21 to 5571 patients or residents, and from 11 to 592 health care staff.…”
Section: Health Care Setting and Populationmentioning
confidence: 99%
“…Sample sizes ranged from 21 to 5571 patients or residents, and from 11 to 592 health care staff. Nine studies included older people (.64 y old) (25,27,29,35,37,39,43,45,48), and nurses or nursing assistants were the most commonly targeted staff group for nutrition training (n = 14 studies) (26,29,33,34,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Health Care Setting and Populationmentioning
confidence: 99%